Yona of the dawn. 44 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Kusanagi, Mizuho, 1979- Yona of the Dawn, 2025)
"Yellow Dragon Zeno has sealed away the other three dragons in the Chalice of the Four Dragons' Blood. He tells Yona and Hak that he wishes to return the four dragons to the heavens and end his life. But is this heartbreaking farewell truly the end of the Dragon Warriors?" --